On reproduction in red algae: further research needed at the molecular level - García-Jiménez, Pilar; Robaina, Rafael R. (Frontiers in Plant Science, 2015)
Multicellular red algae (Rhodophyta) have some of the most complex life cycles known in living organisms. Economically valuable seaweeds, such as phycocolloid producers, have a triphasic (gametophyte, carposporophyte and tetrasporophyte) life cycle, not to mention the intricate alternation of generations in the edible “sushi-alga” nori. It is a well-known fact that reproductive processes are controlled by one or more abiotic factor(s), including day length, light quality, temperature and nutrients. Likewise, endogenous chemical factors such as plant growth regulators have been reported to affect reproductive events in some red seaweeds. Still, in the genomic era and given the high throughput techniques at our disposal, our knowledge about the endogenous molecular machinery lags far behind that of higher plants. Any potential effective control of the reproductive process will entail revisiting most of these results and facts to answer basic biological questions as yet unresolved. Recent results have shed light on the involvement of several genes in red alga reproductive events. In addition, a working species characterized by a simple filamentous architecture, easy cultivation and accessible genomes may also facilitate our task.